Efektivitas Ekstrak Etanol Rimpang Temulawak Sebagai Antibiofilm Terhadap Candida Albicans Penyebab Kandidiasis - WASILATUN NAJAHAH; MASFUFATUN (Universitas Hang Tuah, 2025)
Curcuma (Curcuma xanthorrhiza Roxb) is a type of herbal plant that can be used to control infections from C. albicans, because it contains alkaloids, flavonoids, phenolics, saponins, triterpennoids, and glycosides. The purpose of this study is to analyze the effectiveness of temulawak rhizome ethanol extract as an antibiofilm against Candida alibicans, which causes candidiasis. The research design used is purely experimental with a post test control group only design approach. The extraction method used is maceration with 96% ethanol solvent, the antibiofilm activity test uses the microtiter plate biofilm assay method. The measurement of Optical Density (OD) of the antibiofilm activity test results was carried out with a microplate reader at a wavelength of 595nm. The data was analyzed using SPSS for Windows V29.02. The results showed that Temulawak ethanol extract (Curcuma xanthorrhiza Roxb) had a significant effect on the formation of C. albicans biofilm (p<0.05) with the highest inhibition at a concentration of 1.56%, and the smallest value at a concentration of 50%. The MBIC50 value was determined by probit analysis, so that the concentration of Temulawak ethanol extract (Curcuma xanthorrhiza Roxb) which can inhibit 50% of the formation of C. albicans biofilm is located at a concentration of 0.031%. Thus, it can be concluded that Temulawak rhizome ethanol extract has antibiofilm effectiveness against C. albicans, which causes candidiasis at the stage of biofilm formation. Thus, ethanol extract of temulawak rhizome has the potential to be used as an herbal medicine for the treatment of infectious diseases caused by C. albicans biofilm.